The Effect of Direct-Focused and Unfocused Written Corrective Feedback Toward Freshmen Foreign Language Writing - Muh Junaidi; Marham Jupri Hadi (Humanitatis : Journal of Language and Literature, 2020)
This study aims at finding out the effect of direct-focused and direct-unfocused written corrective feedback in improving freshmen essay writing the use of preposition, article and past tense are investigated in students revision text and new pieces of essay writing. The study uses an experimental method and true-experimental design. Data collected from 60 students for 3 month. Data are analyzed by two-way ANOVAs using SPSS 21. The study found the significant effect of Direct-Focused CF. Likewise, using Direct-Unfocused CF has positive effect. Both groups outperform in revision and new pieces of writing than group without corrective feedback. In addition, there is positive interaction effect among the use of such corrective feedback and exposure. For that reason, it seems that is evidence underpinning the importance of such feedbacks and exposure in increasing students’ writing accuracy at using any grammatical items. Further study needs to be held in order to reveal the relationship or effect of students’ motivation, perception and engagement and typology of feedback in improving students writing performance.